Ways of achieving sustainable land use in Germany: a stocks-based analysis - Fischer, Beate; Jöst, Frank (Sustainability and the art of long term thinking, 2017)
Current land use in Germany - particularly the marked trend towards urban sprawl - is associated with a range of environmental problems. The spread of areas dedicated to human settlements and transport infrastructure (Siedlungs- und Verkehrsfläche) entails the loss of fertile soils for agricultural use. Road building and soil sealing more generally are part of the reason why animal and plant habitats are being destroyed. Decentralised spatial structures (towns and villages scattered throughout the countryside) lead to high volumes of traffic and cause considerable noise pollution and harmful emissions. This is why more sustainable land use is crucial to implementing an environmentally sound form of agriculture as well as preserving biodiversity and combating climate change.